Comparison of the vibration sensors used in the estimation of the combustion process in a diesel engine. (July 2014) - Shaobo, Ji; Yong, Cheng; Wanyou, Huang; Minli, Huang
The vibration signal measured from the cylinder head contains much effective information about the combustion process. The vibration signal can be measured with a vibration displacement sensor, a vibration velocity sensor or a vibration acceleration sensor. In this study the signals measured with the three sensors were compared. The comparison results showed that the vibration displacement measured from the cylinder head is mainly caused by the fixed bracket of the diesel engine, and it is difficult to extract combustion information from the vibration displacement. The vibration velocity signal was compared with the pressure increase rate. The comparison results showed that the two signals have similar trends in the main combustion process. The vibration velocity signal contains much information about combustion. The vibration acceleration signal is hardly influenced by the fixed bracket but contains the vibration response excited by the impact of the opening and closing of the valves and other impact-exciting sources. Based on the results of analyses, it can be concluded that the vibration velocity sensor is the best sensor to estimate the combustion process. The vibration velocity signal was used to estimate the timing of the start of combustion for a two-cylinder homogeneous charge compression ignition engine. The results demonstrated that the accuracy of estimation fulfils the requirement of the application.